LITERARY THEORY AND LITERATURE TEACHING: THINKING THE PLACE OF MAJOIRING IN ARTS FOR THE PREPARATION OF READERS - Santos Pinheiro , Alexandra (Atenas, 2012)
The research on the formation of literary readers, in our view, should cover all elements that structure the literary reading process: access to books, reading public policies, school libraries, literacy practices within and outside the classroom, etc.. In this set of factors that can contribute or not to form literary readers, we add to the urgency of thinking about the place of the university, especially for the present work, the course of Letters, in preparing teachers to be main mediators between the book and potential new readers. Research conducted over two years with students of the senior year of Letters, the Great Dourados Federal University, shows that many mediators of reading, atheoretical form without reading experience. Are new teachers, readers of literature on self-help and without support for more complex readings, the university has sent to the labor market with a mission to encourage literary reading among young people, children and adults. This communication, therefore, to analyze the statements of the students in the course of Arts to understand why future teachers, mediators and trainers unable to build up readership as readers. The conclusion suggests, also in the course curriculum of Arts and proposes some activities for graduation in Arts also be thought of as a place to train readers and even before training teachers.